Retraction: CoH-catalyzed radical hydroalkylation of alkenes with 1, 3-dicarbonyls. Issue 93 (11th November 2022) - Guan, Meihui; Miao, Huanran; Qin, Tao; Zhang, Ge; Zhang, Qian
Abstract : Retraction of 'CoH-catalyzed radical hydroalkylation of alkenes with 1, 3-dicarbonyls' by Meihui Guan et al., Chem. Commun., 2022, 58, 5265–5268, ; https://doi.org/10.1039/D2CC01382G .